2020
DOI: 10.1080/17482631.2020.1785610
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the taboo: eight Swedish clinical psychologists’ experiences of compassion fatigue

Abstract: Purpose: The aim of the study was to investigate the participating psychologists' experiences with compassion fatigue, and to identify individual, interpersonal, and organizational factors and strategies perceived as contributing or protecting in relation to compassion fatigue. Methods: Semi-structured telephone interviews were conducted with eight psychologists (three men and five women) with more than five years of experience in clinical practice. The interviews were analyzed with thematic analysis, generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 26 publications
5
18
0
5
Order By: Relevance
“…Some of the aspects of compassion fatigue, such as a lack of interest in or annoyance with patients, can be particularly difficult to address since they do not fit with the general image of health care professionals as compassionate and altruistic (Isdal, 2017). This theme was also found in the study by Norrman Harling et al (2020), where psychologists expressed concern regarding their own and others' expectations of psychologists as never failing to be compassionate towards others. Other contextual factors hindering compassion were physical and ethical stress due to a heavy workload and complex patient cases combined with hindering organizational factors such as lack of resources, time, and support from higher instances (Norrman Harling et al, 2020).…”
Section: Introductionsupporting
confidence: 58%
See 4 more Smart Citations
“…Some of the aspects of compassion fatigue, such as a lack of interest in or annoyance with patients, can be particularly difficult to address since they do not fit with the general image of health care professionals as compassionate and altruistic (Isdal, 2017). This theme was also found in the study by Norrman Harling et al (2020), where psychologists expressed concern regarding their own and others' expectations of psychologists as never failing to be compassionate towards others. Other contextual factors hindering compassion were physical and ethical stress due to a heavy workload and complex patient cases combined with hindering organizational factors such as lack of resources, time, and support from higher instances (Norrman Harling et al, 2020).…”
Section: Introductionsupporting
confidence: 58%
“…This theme was also found in the study by Norrman Harling et al (2020), where psychologists expressed concern regarding their own and others' expectations of psychologists as never failing to be compassionate towards others. Other contextual factors hindering compassion were physical and ethical stress due to a heavy workload and complex patient cases combined with hindering organizational factors such as lack of resources, time, and support from higher instances (Norrman Harling et al, 2020). Additionally, research by Åhlin (2015) has shown that health care personnel often experience stress due to a troubled conscience when they cannot provide the type of care they wish to provide.…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations